Scientific approach to the 1-h cycling world record: a case study - Padilla, S.; Mujika, I.; Angulo, F.; Goiriena, J. J. (Journal of Applied Physiology, 2000)
The purpose of this study was to describe the physiological and aerodynamic characteristics and the preparation for a successful attempt to break the 1-h cycling world record. An elite professional road cyclist (30 yr, 188 cm, 81 kg) performed an incremental laboratory test to assess maximal power output (W(max)) and power output (W(OBLA)), estimated speed (V(OBLA)), and heart rate (HR(OBLA)) at the onset of blood lactate accumulation (OBLA). He also completed an incremental velodrome (cycling track) test (VT1), during which V(OBLAVT1) and HR(OBLAVT1) were measured and W(OBLAVT1) was estimated. W(max) was 572 W, W(OBLA) 505 W, V(OBLA) 52.88 km/h, and HR(OBLA) 183 beats/min. V(OBLAVT1), HR(OBLAVT1), and W(OBLAVT1) were 52.7 km/h, 180 beats/min, and 500.6 W, respectively. Drag coefficient and shape coefficient, measured in a wind tunnel, were 0. 244 and 0.65 m(2), respectively. The cyclist set a world record of 53,040 m, with an estimated average power output of 509.5 W. Based on direct laboratory data of the power vs. oxygen uptake relationship for this cyclist, this is slightly higher than the 497. 25 W corresponding to his oxygen uptake at OBLA (5.65 l/min). In conclusion, 1) the 1-h cycling world record is the result of the interaction between physiological and aerodynamic characteristics; and 2) performance in this event can be predicted using mathematical models that integrate the principal performance-determining variables.